Bridging the Gap: A Study on Enhancing Accessibility and Accuracy in Scientific Lay Summaries - Blais, Tehani; Bonilla, Monalisa; Elfizy, Maya; Ramahi, Leen (SciWise, 2025)
Manuscript presenting research on scientific lay summaries done in Dr. Katie Moisse’s course SCICOMM 2A03